ANALISIS PENGEMBANGAN CRITICAL CRAFT TRAINING DATABASE PADA DEPARTEMEN QHSES DI PT. MCDERMOTT INDONESIA_OKE - Inayah Alifia Fajar; Yuli Indah Fajar Dini (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
Being the most important part in helping and carrying out company activities is the role of an admin. The QHSES Department training at PT. McDermott Indonesia plays a very important role in creating and increasing the performance and productivity of all employees. During the process of this practical work activity, the author made an update on the database by creating a section to enter data values as well as information on employee content which aims to create work effectiveness and efficiency. The technique used is the observation technique that is measuring the observed object by recording various phenomena that occur. The development of this database helps the admin to be able to input data and information in a more detailed and clear manner and minimizes difficulties in finding employee training information and evidence of employee competence when an incident occurs in the fabrication area.